2022
DOI: 10.3390/foods11050741
|View full text |Cite
|
Sign up to set email alerts
|

The Modelling of Convective Drying Variables’ Effects on the Functional Properties of Sliced Sweet Potatoes

Abstract: Drying is a commonly used technology that provides a long post-harvest storage time for produce such as sweet potatoes. Convective drying (CD) is a method that, when conditions are optimized, provides produce with a better appearance and improved textural properties. In this study, changes in water activity (aw), moisture content (MC), rehydration capacity (Rc), shrinkage (Sb) and color attributes were modelled for the optimization of drying factors (temperature, thickness and time) using response surface meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…Furthermore, the convectively tray-dried spine gourd (Momordica dioica) slices (2.5-3 mm thick) dried at 40-70 °C presented a signifcant (p < 0.05) diference in the L * value ranging from 78.55 ± 0.66 to 83.74 ± 0.14 [19]. In the same way, the drying temperature of (45-75 °C) and sweet potato slice thicknesses (2-6 mm) had a signifcant (p < 0.05) efect on the L * , C * , and h o values of tray-dried sweet potatoes [34].…”
Section: Fourier Transform Infrared Spectrophotometer (Ftir)mentioning
confidence: 66%
See 3 more Smart Citations
“…Furthermore, the convectively tray-dried spine gourd (Momordica dioica) slices (2.5-3 mm thick) dried at 40-70 °C presented a signifcant (p < 0.05) diference in the L * value ranging from 78.55 ± 0.66 to 83.74 ± 0.14 [19]. In the same way, the drying temperature of (45-75 °C) and sweet potato slice thicknesses (2-6 mm) had a signifcant (p < 0.05) efect on the L * , C * , and h o values of tray-dried sweet potatoes [34].…”
Section: Fourier Transform Infrared Spectrophotometer (Ftir)mentioning
confidence: 66%
“…Te main efect of tray-drying temperature and sample thickness (A and B) and the quadratic efect of tray-drying temperature (A 2 ) signifcantly (p < 0.05) afected the a w of banana four (Table 3). In the same way, Savas [34] reported that the convective drying of sweet potato slices at diferent temperatures (45-75 °C) and sweet potato slice thicknesses (2-6 mm) showed a positive reduction in the a w with an increase in drying temperature and a decrease in sample thickness.…”
Section: Water Activity (A W )mentioning
confidence: 68%
See 2 more Smart Citations
“…The increase in phenolic content could also be explained, at least partially, by the formation of Maillard reaction products with a phenolic-type structure during the thermal process [ 98 ]. A recent study carried out by Savas [ 99 ] compared the effect of freeze-drying and convective drying on the TPC, total flavonoids, and total anthocyanins in sliced sweet potatoes. The TPC and total flavonoid content in freeze-dried samples, and total anthocyanin content in convectively dried samples were clearly higher than in fresh tubers.…”
Section: Effect Of Sweet-potato Processing On Phenolic Compoundsmentioning
confidence: 99%